Investigating the effect of polymer-surfactant complexes on the flow behaviour in pipelines - Ang, Ming Key (2014)
Transporting liquids in strategic pipelines is usually occur in turbulent flow mode and that is considered as one of the most power consuming sectors in the industry when most of the pumping power is dissipated in the turbulent flow structures formed during transportation. Frictional drag formed within fluid in pipelines can be reduced spectacularly by adding minute amount of additives which is known as the drag reducing agent. These drag reducing agents can enhance flow performance by restricting the formation of drags and eddies at high shear forces along pipeline system. In the present work, drag reduction efficiency were studied by examining two similarly charged polymer (algin) and surfactant (Sodium Stearate) and its complexes in a rotating disk apparatus (RDA). The drag reduction performance will be evaluated by analysing the effect of solution viscosity and its corresponding torque exerted on RDA device for laminar and turbulent state. For this research, experiments were conducted using water as the testing fluid. From the experimental work, the highest drag reductions achieved from individual additives was 15.12 % and 23.63% for 600 ppm polymer, and 600 ppm surfactant respectively. Further testing was performed by evaluating the complexes. Whereas the highest drag reduction obtained for the complexes are found to be 25.54% from a 600 ppm 600 ppm polymer-surfactant complexes. Similarly charged polymer- surfactant can enhance flow performance by reducing the drag at adequate viscosity